Analysis of circulating microRNAs in patients with repaired Tetralogy of Fallot with and without heart failure - Abu-Halima, Masood (J Transl Med, 2017)
BACKGROUND: MicroRNAs (miRNAs) are a class of regulatory RNAs that regulate gene expression post-transcriptionally. Little, however, is known on the expression profile of circulating miRNAs in Tetralogy of Fallot (TOF) patients late after surgical repair. In this study, we aimed to identify the specific patterns of circulating miRNAs in blood of patients with repaired, non-syndromic TOF and to assess whether these specific miRNAs may be useful to differentiate patients with and without heart failure. METHODS: SurePrint™ 8 × 60 K Human v16 miRNA arrays were used to determine miRNA expression profiles in 15 healthy controls and 37 patients after TOF repair of whom 3 had symptomatic right heart failure. The expression levels of selected miRNAs have been validated by quantitative reverse transcription polymerase chain reaction (RT-qPCR). Enrichment analyses of altered miRNA expression were predicted using bioinformatic tools. RESULTS: Compared with healthy controls, a total of 49, 58 and 77 miRNAs were found to be significantly altered in TOF patients (TOF-all), TOF patients with (TOF-HF) and without symptomatic right heart failure (TOF-noHF) (>2.0-fold change, adjusted P < 0.05), respectively. Three miRNAs namely miR-181d-5p, miR-206 and miR-625-5p were validated by RT-qPCR in all TOF groups. The area under the receiver operating characteristic curve (AUC) for miR-181d-5p, miR-206 and miR-625-5p were 0.987, 0.993 and 0.769 in TOF-all and 0.990, 0.994 and 0.749 in TOF-noHF, respectively. Moreover, expression levels of miR-625-5p, miR-1233-3p and miR-421 were lower in TOF-HF compared to TOF-noHF (P = 0.012). CONCLUSIONS: Altered expression levels of circulating miRNAs were found in TOF patients late after surgical repair and are different to those seen in the right ventricular myocardium of infants with TOF. Expression levels of miR-421, miR-1233-3p and miR-625-5p are lower in TOF patients with symptomatic right heart failure and thus may indicate disease progression in these patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-017-1255-z) contains supplementary material, which is available to authorized users.